Maksymilian Studniarski – poznański społecznik i nauczyciel - Gucia, Dobrosława; Wojtczak, Jakub (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2022)
Maksymilian Studniarski, a teacher and an involved citizen from Poznań, a co-founder and member of the Poznań Society for the Advancement of Arts and Sciences (PTPN), has slipped to oblivion. To date, a biography of the first conserver-restorer and custodian of the collection of the PTPN Museum has not been written. This article presents his life and focuses on the most important facts in it, the functions he performed in various societies, his academic and popular-science activity as well as the history of his family – the ancestors and descendants alike.